BI 1015550: an investigational phosphodiesterase 4B (PDE4B) inhibitor for lung function decline in idiopathic pulmonary fibrosis (IPF). (2nd January 2023) - Sgalla, Giacomo; Simonetti, Jacopo; Cortese, Stefania; Richeldi, Luca
ABSTRACT: Introduction: The two available therapies for idiopathic pulmonary fibrosis (IPF), pirfenidone and nintedanib, slow down but do not halt IPF progression. Therefore, several agents with specific molecular targets have been recently investigated to find a cure for IPF. Phosphodiesterase 4 (PDE4) inhibition is known for its anti-inflammatory and antifibrotic properties. BI 1015550, an oral preferential inhibitor of the isoform PDE4B, could express complementary activity to current therapies in IPF and other forms of progressive pulmonary fibrosis. Areas covered: In this review, we first provide an overview toof the current IPF treatment market, followed by the description of pharmacokinetics and pharmacodynamics of BI 1015550. The main preclinical and early clinical evidence on BI 1015550 is then described, as well as its potential as an IPF treatment. Expert opinion: Oral treatment with BI 1015550 was shown to stabilize lung function as compared to placebo over 12 weeks, both among patients with and without background antifibrotic use, with an acceptable safety profile in a phase 2 trial, and a phase 3 trial has been initiated. To date, this represents to date the largest effect size for an IPF investigational drug tested in a phase 2 trial with the shortest duration.